Pitfalls in Diagnosing Heterotopic Pregnancy in Sub-Saharan Africa: A Case Report at the Yaounde University Teaching Hospital (Cameroon) - Andre Ngandji Dipanda; Jovanny Tsuala Fouogue; Valere Koh Mve; Bruno Kenfack; Jean Dupont Ngowa Kemfang (Hindawi Limited, 2021)
Heterotopic pregnancy (HP) is a dizygotic twin pregnancy in which one gestational sac is intrauterine and the other is extrauterine. The prevalence of HP is unknown in Cameroon where the diagnosis is difficult and usually fortuitous like in other resource-poor settings. We herein depict pitfalls and delays in the diagnosis and management of a ruptured heterotopic pregnancy at the Yaounde University Teaching Hospital. After a wrong diagnosis and inadequate treatment, our patient presented at our emergency unit with severe pelvic pain and clinical signs of hemoperitoneum with shock. She underwent a total left salpingectomy through laparotomy. She had a complete spontaneous abortion five days after the surgery. Given that sonography is not routinely available in emergency departments in resource-poor settings, it may be relevant for practitioners to always bear HP in mind when facing ruptured ectopic pregnancies.